As representações sociais: análise temporal em função da existência da legislação das áreas de proteção e recuperação dos mananciais (APREM) do município de São Carlos-SP -Bacia Hidrográfica do Ribeirão do Feijão (BHRF) - Galvão, Davi Fortes (Universidade Federal de São Carlos, 2018)
The reflection about social practices in an urban context marked by the permanent deterioration of the built environment and its ecosystem can not dispense with the analysis of the determining factors of the process and its actors and of the forms of social organization. This study evaluated whether the Law of Areas of Protection and Recovery of Waters (APRW) that contributed significantly to the environmental conservation of the Ribeirão do Feijão Watershed (RFW) in the municipality of São Carlos during its period of validity (2006 to 2016) the link between human activities, the local social context, land use change and the effects of these dynamics on the conservation of the environment, thus providing a basis for the sustainable use and management of the environmental resources of São Carlos (SC) and other regions. Interviews with local residents and specialists, raised the social representations (SR) attributed to RFW analyzing what SR can express about the thoughts and relationships that individuals maintain with the organs with the state and with environmental laws. These expressions gave meaning to the perception of the local population about the state of conservation of the vegetation of the surroundings of where they live. The verification of the effectiveness of the APRW Law and its influence on the conservation of the RFW-SC was facilitated by geographic information systems tools that obtained data from the years of 2006, 2011 and 2016 comparing this data among themselves and also with neighboring municipalities (Itirapina and Analândia) that are also part of the RFW under the influence of the law APRW. There was a difference between the SR of the local residents, focused mainly on their productive and subsistence activities, and SR of the specialists, focused on urban supply. These differences in SR on the RFW generate conflicts since the specialists are also responsible for drafting environmental laws in the RFW that the local residents are subject to. The SRs raised by the interviews with the local residents of the RFW demanded new analyzes on SR, highlighting the most impactful to the environment (more impactful social representations - MISR) and the less impactful social representations (LISR). The MISR are related to subsistence, supplies and domestic use, while LISR refer to RFW as an affective site, linked to the following approaches: 1) well-being and admiration, 2) environmental dynamics and 3) water is life. Regarding the analyzes of the land use and cover data, it can be observed that in the period between 2006 (still without the influence of the APRW law) and 2016, that the forest areas in the RFW-SC increased by 36.89% (from 25.94% of the area to 35.51%). In the part of RFW-Itirapina / Analândia, forest vegetation increased from 16.02% to 18.83%, a relative increase of 17.54%.Regarding the permanent preservation areas (PPAs) in the RFW-SC under the jurisdiction of the APRW law, it was found that in the same period, the areas of PPAs had an increase of 16.42%, and in the RFW Itirapina / Analândia an increase of 11.1%. The environmental perception regarding the conservation status of the forest was consistent with the results of the survey, in which 53.85% of the interviewed residents believed that the forest vegetation is increasing, 26.92% said that it remained stable and 19.23% believed that the vegetation is decreasing. Regarding the importance of the inspection bodies, 69% of the interviewed local residents believe that they are important for environmental conservation, 23% for guidance and environmental education, and 8% have shown repulsion to these bodies. As for the knowledge of the APRW law by the residents, none of the interviewees seemed to know it; just have some knowledge regarding protection of APPs and cutting of trees in general.
The social representations: temporary analysis in the function of the existence of the legislation of the areas of protection and recovery of the manantial (APREM) of the municipality of São Carlos-SP-Hydrographic Bacon of the Ribeirão do Feijão (BHRF)
Keywords: Bacia Hidrográfica; Representações sociais; Legislação ambiental; Watershed; Social representations; Environmental legislation; CIENCIAS HUMANAS::GEOGRAFIA